The Influence of Internal Control on Employee Performance With Reward System as a Moderating Variable - Nugrahadi Fajria Irawan (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study aims to determine the ability of the reward system in moderating the influence of internal control on employee performance at PT.Kawan Era Baru Bandung Branch. The factors tested in this study are the independent variable is internal control, the dependent variable is employee performance, while the moderating variable is the reward system. The research method used is the explanatory method. The population in this study were employees at PT.Kawan Era Baru Bandung Branch. The sampling technique used is non-probability sampling technique with purposive sampling technique so that the number of samples is 96 employees. The analytical method used is moderated regression analysis using the SPSS Version 23.00 program. The results showed that internal control and reward systems affect employee performance, and the reward system can moderate the relationship between internal control and employee performance at PT.Kawan Era Baru Bandung branch. In addition, the magnitude of the influence of internal control, reward system, and interaction moderation in contributing to employee performance is 65.6%.